Analysis of Room Facilities Impact on Guest Satisfaction: A Key Competitive Advantage for Hotels Amid Economic Globalization : Analysis of Room Facilities Impact on Guest Satisfaction: A Key Competitive Advantage for Hotels Amid Economic Globalization - Dina Mayasari Soeswoyo; Robiana; Sekti Rahardjo (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2024)
In the context of economic globalization, intense competition in Indonesia's hospitality sector compels local companies to understand customer behavior. This research emphasizes the crucial role of room facilities in shaping guest satisfaction, a key factor in maintaining and enhancing competitiveness. A quantitative research method employing surveys, Likert scales, and statistical analysis was used to identify the influence of room facility quality at Hotel Soliga on guest satisfaction. Results indicate that the majority of respondents provided positive assessments of room facilities. Hypothesis testing suggests a positive and significant impact of room facilities into guest satisfaction, although the explained variance in guest satisfaction attributed to these variables is relatively low. In conclusion, room facilities have a tangible influence, and hotel management is advised to consider improvements to enhance guest satisfaction, potentially contributing to the hotel's reputation and sustainability.